Composites of polypropylene with layered Mg-silsesquioxanes show an unusual combination of properties - Kumaraswamy, Guruswamy; Deshmukh, Yogesh S.; Agrawal, Vikrant V.; Nisal, Anuya (Industrial & Engineering Chemistry Research, 2008)
We report the synthesis of vinyl modified magnesium silsesqiuoxanes (''vinyl clay''), and the formation of their composites with isotactic polypropylene (iPP) by melt compounding. Vinyl clay is a layered compound with a layer thickness of approximately 1 nm. Vinyl clay does not exfoliate in iPP; rather, it disperses to form a network that exhibits a characteristic low frequency solid-like plateau in the elastic modulus in dynamic melt theological measurements. Strangely, vinyl clay also plasticizes iPP-there is a decrease in the high frequency complex viscosity. The decrease in the complex viscosity is higher at higher frequencies, suggesting the influence of slip at the iPP-vinyl clay interface. The combination of the low frequency elastic plateau and plasticization makes the vinyl clay composite significantly more shear thinning than the matrix iPP. In the solid state, vinyl clay-iPP composites exhibit increased tensile modulus (showing approximate to 50% increase for a 5% loading), but surprisingly, no corresponding decrease in the elongation at break. Thus, while microstructural characterization indicates that only a small fraction, if any, of the vinyl clay is exfoliafed, the enhancement in mechanical properties is similar to that observed for iPP-exfoliated montmonillonite nanocomposites. Our compounding protocol is unable to effectively disperse the clay in the iPP at clay loadings greater than about 7.5%. Therefore, the low frequency plateau in the melt elastic modulus and the solid tensile modulus increase with clay loading until 7.5% but exhibit a nonmonotonic decrease at higher clay loadings.